Clontuskert Augustinian Priory, stone store, mullion fragment - O'Donovan, Danielle (My University, 2009)
Mullion, loose in stone store, only one side of the mullion has elaborate mouldings, the other side is simply chamfered. The moulded side comprises: central fillet flanked at either side by hollow chamfer, spike, hollow chamfer.
Keywords: Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Architecture, Augustinian; Tracery (Architecture); Late Medieval; moldings, hollow; mullions